PERBAIKAN KUALITAS PELAYANAN PENGGUNA BPJS MENGGUNAKAN METODE FUZZY- SERVQUAL - Erniyani; Hasdir, Nita Aulia (JURNAL REKAYASA SISTEM INDUSTRI, 2023)
A hospital is a health service provider that experiences an increase in the number of patients every year. Every patient expects good quality service. This, if there is a discrepancy between satisfaction and expectations, will result in the hospital's reputation by reducing the number of patients seeking treatment at that place. Therefore, this research aims to evaluate the quality of service for BPJS users referring to five dimensions, namely tangible, reliability, responsiveness, assurance, empathy. The servqual method is used to determine service quality by measuring the level of gap between satisfaction and what is expected based on the results of the questionnaire. The aim of combining the fuzzy servqual method is to produce accurate values. The results of the research show that there are six attributes that have negative values, namely the ability of hospital staff to provide timely services (C4), doctors having experience treating patients (D1), hospital staff and doctors dressing cleanly, neatly and wearing PPE (A3), comfortable waiting room facilities (A4), availability of all types of services (C3), and providing security guarantees while the patient is being treated (D2). However, the most significant attribute is C4 with a value of -1.00. This shows that there is a need to improve the quality of these six attributes so that they can increase the level of patient satisfaction at Hospital X